Makna Metafora Lirik Lagu dalam Album Monokrom Produksi Tulus Company (Pendekatan Metafora Lakoff dan Johnson) - Cahyani, Mintresia Astri; Azis, Azis; Agussalim, Andi (Nuances of Indonesian Language, 2025)
This research aims to analyze the meaning of metaphor in the song lyrics on the album "Monokrom" produced by Tulus Company in 2016 using the conceptual metaphor approach proposed by George Lakoff and Mark Johnson. Conceptual metaphors are an important tool in understanding how humans process experience and understand the world through language. This research is descriptive qualitative research using note-taking techniques. The data source for this research is the song lyrics in the Monokrom album produced by Tulus Company. The data analysis technique used is the Miles and Huberman qualitative data analysis technique, namely data reduction, data presentation, and drawing conclusions. The song lyrics in the album "Monochrome" are analyzed to identify and interpret the metaphors contained therein. The data obtained was then categorized based on the types of conceptual metaphors according to Lakoff and Johnson's theory. The research results show that the album uses many types of metaphors to convey messages and emotions in the songs, such as structural, orientational and ontological metaphors. Based on the research results obtained, the use of metaphor in the lyrics of this song provides depth of meaning and enriches the listener's aesthetic experience and also contributes to linguistic studies, especially in understanding the context that figurative language can be used in song lyrics to convey complex and emotional meaning.